URGENSI PENDIDIKAN SEKS MENURUT IMAM NAWAWI AL-BANTANI DALAM KITAB UQUD AL-LUJAINI (INTISARI Q.S. AN- NUR AYAT 58-61) - Mumu (HASBUNA : Jurnal Pendidikan Islam, 2022)
The purpose of this study was to determine the urgency of sex education according to Imam Nawawi Al-Bantani in the book Uqud Al-Lujaini, to find out the urgency of sex education according to Q.S An-Nur verses 58-61, and to find solutions to prevent deviant sexual behavior. This research uses this type of research. Study This type of research uses qualitative research with library methods (library research). The results of this study include, among other things, the nature of sex education, the purpose of sex education, the benefits of sex education and sex education materials. The solution to preventing sexual deviant behavior is to provide sex education from an early age or at least at school age by providing an understanding of the correct sex theories in children